From Humaneness to the Trend of Humanization in Vietnamese Criminal Law - Thuy, Vu Thi (VNU Journal of Science: Legal Studies; Vol 41 No 2, 2025)
In the ongoing progress of humanity, as human rights and humanitarian values are increasingly emphasized, humaneness has become an essential principle in the development of modern criminal law. It is not merely a legal principle but a vivid expression of compassion, tolerance, and a commitment to rehabilitation over punishment. The spirit of humaneness promotes fair and compassionate treatment of offenders, aiming to reform and restore human dignity rather than to exact retribution. Globally, the trend toward the humanization of criminal law is gaining momentum through the reduction of harsh punishments, the expansion of non-custodial measures, and the enhancement of reintegration support. In Vietnam, this trend not only reflects the spirit of legal reform but also affirms the nation’s deep-rooted humanitarian tradition. This article clarifies the relationship between humaneness and the trend of humanization, an underlying current of thought that nurtures the progress of a modern criminal justice system.